2020
DOI: 10.1002/advs.202001724
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic State and Cell Identity Combinatorially Dictate the Susceptibility of Cells within Glioma Development Hierarchy to IGF1R Targeting

Abstract: Glioblastoma is the most malignant cancer in the brain and currently incurable. It is urgent to identify effective targets for this lethal disease. Inhibition of such targets should suppress the growth of cancer cells and, ideally also precancerous cells for early prevention, but minimally affect their normal counterparts. Using genetic mouse models with neural stem cells (NSCs) or oligodendrocyte precursor cells (OPCs) as the cells‐of‐origin/mutation, it is shown that the susceptibility of cells within the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…We have previously used this system to examine the division pattern of OPCs after acquiring glioma‐relevant mutations. [ 15 , 51 ] Therefore, we used tamoxifen‐inducible NG2‐Cre ERT to induce mitotic recombination directly in OPCs at P3 and examine the clonality of labeled cells. We confirmed that only OPC‐lineage cells could be labeled in the system and that the labeling was fully dependent on the presence of tamoxifen (data not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously used this system to examine the division pattern of OPCs after acquiring glioma‐relevant mutations. [ 15 , 51 ] Therefore, we used tamoxifen‐inducible NG2‐Cre ERT to induce mitotic recombination directly in OPCs at P3 and examine the clonality of labeled cells. We confirmed that only OPC‐lineage cells could be labeled in the system and that the labeling was fully dependent on the presence of tamoxifen (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Knockout of NF1 in OPCs or neural progenitors resulted in dramatic overexpansion of OPCs at the population level. [ 54 , 55 , 56 , 57 ] Therefore, we examined whether NF1 deficiency could prevent the loss of ventrally derived OPCs during development.…”
Section: Resultsmentioning
confidence: 99%
“…One clinically relevant application of MADM is the tracing of tumor growth upon sparse or clonal ablation of tumor suppressor genes and/or to assay for the effects of therapeutic agents. As such, MADM has been used for the analysis of tumor formation and the delineation of cancer cell of origin at the single-cell level in the brain and distinct organs (Muzumdar et al, 2007(Muzumdar et al, , 2016Liu et al, 2011;Gonzalez et al, 2018;Tian et al, 2020;Yao et al, 2020).…”
Section: Mosaic Analysis With Double Markersmentioning
confidence: 99%
“…Our results indicated that IFN-β affected hGSCs rather than hNSCs. hNSCs are considered to be the most likely initiation cells of malignant glioma [17,25,26]. On the other hand, hNSCs have been considered efficient vehicles for the delivery of anti-cancer agents to tumor sites during therapeutic applications [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…During malignant glioma treatment, at least two aspects of NSCs are related to GSCs. On the one hand, mutated NSCs are considered to be the initiation cells of glioma [17,25,26]. On the other hand, normal NSCs are considered to have the ability to move towards GSCs, and can be used as carriers for the treatment of gliomas [27,28].…”
Section: Introductionmentioning
confidence: 99%